Pemanfaatan Aplikasi Quizizz sebagai Media Pembelajaran Matematika di Sekolah Dasar Islam di Karawang - Lela Monika; Fadilah Prabowo; Fitri Yessi Jami (Syntax Corporation Indonesia, 2024)
This research aims to determine the use of the Quizizz application as a mathematics learning medium in elementary schools and to determine the supporting and inhibiting factors in the use of the Quizizz application as a learning medium in the Karawang Islamic Elementary School. This research was conducted on elementary school students with 3 class teachers, 3 class 1A students, 3 class 1B students and 3 class 1C students as participants. The research method used uses a descriptive method with a qualitative approach using interview, observation and documentation data collection techniques. However, based on data obtained from interviews, the Quizzizz application can help educators and students carry out teaching and learning activities in a more interesting and interactive manner, although there are supporting and inhibiting factors in using the Quizzizz application, learning continues according to the plan that has been prepared in RPP using Quizizz media.